Psychological Distress in Chimpanzees Rescued From Laboratories. Issue 4 (8th August 2015) - Lopresti-Goodman, Stacy M.; Bezner, Jocelyn; Ritter, Chelsea
Abstract : The United States is one of the last countries allowing invasive research on chimpanzees. Biomedical research on chimpanzees commonly involves maternal deprivation, social isolation, intensive confinement, and repetitive invasive procedures. These physically harmful and psychologically traumatic experiences cause many chimpanzees to develop symptoms of psychopathology that persist even after relocation from laboratories to sanctuaries. Through semistructured interviews with chimpanzee caregivers, direct behavioral observations, and consultation of laboratory records, we were interested in qualitatively analyzing symptoms of psychological distress in a sample of 253 chimpanzees rescued from biomedical research now residing at an accredited chimpanzee sanctuary. We present the results of this analysis and include an illustrative case study of one rescued chimpanzee who engages in self-injurious behaviors and meets modified Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria for posttraumatic stress disorder. We discuss our results in light of recent policy changes regarding the use of chimpanzees in biomedical research in the United States and their implications for those involved in the rescue and rehabilitation of chimpanzees from biomedical research.